VD_FINDINFO Pron / 2012 / 72 vom 3. April 2012 - VD Tribunal cantonal (2012)
OPPOSITIONPROCÉDURE, CHOIXEN GÉNÉRAL, CONSEIL LÉGALPERSONNE, PROCÈS DEVENU SANS OBJET | 379 CC, 388 al. 2 CC, 388 CC, 489 CPC